2016
DOI: 10.1016/j.ccell.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

CD98-Mediated Adhesive Signaling Enables the Establishment and Propagation of Acute Myelogenous Leukemia

Abstract: SUMMARY Acute myelogenous leukemia (AML) is an aggressive disease associated with drug resistance and relapse. To improve therapeutic strategies, it is critical to better understand the mechanisms that underlie AML progression. Here we show that the integrin binding glycoprotein CD98 plays a central role in AML. CD98 promotes AML propagation and lethality by driving engagement of leukemia cells with their microenvironment and maintaining leukemic stem cells. Further, delivery of a humanized anti-CD98 antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 56 publications
3
97
0
Order By: Relevance
“…This supports the idea that most anti-CD98 antibodies act through antibody-dependent cellular cytotoxicity (ADCC) (60), rather than by inhibiting amino acid transport per se. Nonetheless, these antibodies may still block the binding of known partners to the ED (62,63). The recently characterized humanized antibody, IGN523, exhibits robust anti-tumor activity through ADCC (60), and its epitopes are predicted to be different from those presented here.…”
Section: Anti-cd98 Antibodies and Epitopesmentioning
confidence: 91%
“…This supports the idea that most anti-CD98 antibodies act through antibody-dependent cellular cytotoxicity (ADCC) (60), rather than by inhibiting amino acid transport per se. Nonetheless, these antibodies may still block the binding of known partners to the ED (62,63). The recently characterized humanized antibody, IGN523, exhibits robust anti-tumor activity through ADCC (60), and its epitopes are predicted to be different from those presented here.…”
Section: Anti-cd98 Antibodies and Epitopesmentioning
confidence: 91%
“…l ‐Type amino acid transporter 1 (LAT1) is the first identified CD98lc, and cancers from several tissues express both CD98hc and LAT1 proteins. The oncogenicity of CD98 was confirmed with wild‐type CD98hc bound to CD98lc, but not with mutated CD98hc lacking the cysteine residue needed for the association with CD98lc.…”
Section: Introductionmentioning
confidence: 99%
“…Although the major targets of existing anticancer therapeutic antibodies are receptor‐type tyrosine kinases, overexpression of anti‐HER1 and anti‐HER2 is limited to cancers from squamous or glandular epithelium, respectively. As CD98/LAT1 is expressed by almost all cancers irrespective of tissue origin, anti‐CD98/LAT1 therapeutic antibodies may be ideal against numerous human malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the overexpression of CD98 is associated with poor prognosis for cancer patients, thus rendering it a promising tumor target for diagnosis and therapy. Indeed, treatment of patient‐derived AML cells and of established human lymphoma cell lines with a clinical stage humanized anti‐CD98hc monoclonal antibody (mAb IGN523) was shown to block cancer growth in xenograft studies …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, treatment of patient-derived AML cells and of established human lymphoma cell lines with a clinical stage humanized anti-CD98hc monoclonal antibody (mAb IGN523) was shown to block cancer growth in xenograft studies. 12 Beyond implications for cancer therapy, recent studies identified CD98hc as a novel transcytosis receptor at the blood-brain barrier (BBB), which appears suitable for the noninvasive drug delivery to the brain via the molecular Trojan horse strategy. 13,14 In this approach, the transport of a systemically administered therapeutic agent across the BBB into the parenchyma is enabled by fusion with a specific binding protein for the transcytosis receptor.…”
Section: Introductionmentioning
confidence: 99%